Neurotization indicators and state of mental desadaptation in personnel of internal affairs organs - Vyshnichenko S.I. (Medičnì Perspektivi)
The article describes the data of psychological testing of personnel of internal affairs organs, using LNP test: levels of neuroticism and psychopathsation, prevalence of levels of neuroticism among the personnel, the relationship between neuroticism level and clinical groups (mentally healthy, with burnout syndrome and with non-psychotic mental disorders). Level of neuroticism reflects both dynamic and static (states and properties) personality characteristics, i.e. neuroticism is elective personality variable. The clinical picture is characterized by manifestations of asthenonevurotic and psycho-vegetative syndromes. More often among those with non-psychotic mental disorders a high (100%) level of neuroticism, increased (87.5%) and in the zone of uncertain diagnosis (50%) occur, than among those with burnout syndrome, and lower than normal (36.36%) and low (19.08%) neuroticism level – more often among with burnout syndrome, than in those with non-psychotic mental disorders. Level of neuroticism on the verge of normal and pathological conditions occurs mostly in people with burnout syndrome (50%) and non-psychotic mental disorders (50%).